(untitled) (Research, Society and Development, 2021)
Biodegradable polymers undergo a degradation process resulting from the action of microorganisms such as bacteria, fungi and algae. Poly(butylene adipate co-terephthalate) (PBAT) is considered a biodegradable synthetic polymer, even if its degradation has been confirmed under industrial composting conditions, the investigation of its degradation in the marine environment is still limited. Therefore, this work aims to study the biodegradation in the marine environment, of the biodegradable polymer (PBAT), and for that, it was submerged in a static system, using seawater from the coastal region of Pernambuco/Brazil as a fluid. The samples were studied by chemical, thermal and microbiological analyses, after 7, 14, 30, 90, 120 and 180 days of immersion. Microbiological analyzes indicated that aerobic heterotrophic bacteria (AHB), anaerobic heterotrophic bacteria (AnHB) and iron precipitating bacteria (IPB) were quantified in the system at all times at high concentrations, with the exception of Sulfate reducing bacteria (SRB), fungi and Pseudomonas that showed lower concentrations compared to other bacterial groups. Biodegradation was observed by the percentage of mass loss of approximately 2.25%. In the DSC, the expansion of melting peaks after exposure to the marine environment was noted, while the TGA did not show changes in the curve trends. The FTIR showed that no new band appeared, nor displacement, since the vibrations of the covalent bonds of the groups are present regardless of the biodegradation. Indicating that no significant microbiological degradation of PBAT was observed.